Factors associated with transient bradycardia during local anesthesia administration to the oral cavity under intravenous sedation: A retrospective cohort study - Ryo Wakita; Yukiko BaBa; Haruhisa Fukayama; Shigeru Maeda (Elsevier, 2024)
Background/purpose: The possibility of triggering the trigeminocardiac reflex (TCR) during oral surgery is considerably lower than that during other surgeries. A reduced heart rate (HR) of ≥20% from baseline is usually considered a diagnostical criterion for the TCR. Our automated anesthesia charting system often revealed cases of slight transient HR decrease during sedation. We aimed to explore its incidence and associated factors during local anesthesia administration under intravenous sedation. Materials and methods: This study analyzed the data of 2636 cases that received infiltration anesthesia under intravenous sedation from 2008 to 2010 and had vital signs recorded using an automated anesthesia charting system. Especially, data concerning the average HR before anesthesia and the minimum HR between the initiation and end of anesthesia from anesthetic records were extracted. Moreover, data regarding patients' medical history and unusual reactions during dental treatment were collected. Multivariate logistic regression analysis was performed to identify factors associated with transient bradycardia (TB). Results: TB occurred in 472 patients (17.9%); no patient developed hypotension or any associated symptoms, suggesting that intravenous sedation was effective in stabilizing vital signs. The factors associated with TB were younger age, gag reflex, and allergy to local anesthetics. There were no differences in sex, patient history, or dose of sedatives between patients with TB and those without TB. Conclusion: The incidence of TB during infiltration anesthesia under sedation was found to be higher than that previously reported. Additionally, young age and gag reflex were identified as factors associated with bradycardia development.